Development of Smart Board Spinner Media as a Stimulation of Numeracy Skills for 5 to 6 Year Old Children - Sari, Dewi Novita; Iriyanto, Tomas; Maningtyas, Rosyi Damayani Twinsari (Universitas Negeri Malang, 2024)
Children have difficulty mastering the concepts of addition and subtraction as well as number recognition if they have poor numeracy skills and are not stimulated with learning aids. This is the reason for conducting research on the development of learning media. This research aims to present the findings of the development of the learning product